Solitary Myofibroma of the Bladder Trigone in a 3-Month-Old Patient: First Case Report. (3rd May 2016) - Pensabene, Marco; Siracusa, Fortunato; Rodolico, Vito; Li Voti, Giuseppe; Zambaiti, Elisa; Cimador, Marcello
Abstract : Visceral solitary myofibromas are uncommon in childhood. We report a case of a solitary asymptomatic visceral myofibroma of the bladder trigone occurring in a 3-month-old boy. Once malignancies were ruled out by cystoscopy, radical excision was performed in order to avoid any potential impairment of bladder dynamic. Postoperative course was uneventful and patient was discharged on day 3 after surgery. After 36 months of follow-up, the patient is toilet-trained and remains well; bladder function is normal.